Seroepidemiology of the hepatitis B and delta in the southeast of Chiapas, Mexico - Alvarez-Muñoz, T; Bustamante-Calvillo, E; Martínez-García, C; Moreno-Altamirando, L; Guiscafre-Gallardo, H; Guiscafre, J P; Muñoz, O (Archivos de investigacion medica, 1989)
An area of high endemicity for hepatitis B and delta antigen was identified in the southern border of Mexico (Chiapas). The study included individuals from mexican communities and guatemalan refugee camps. 91.1% of the subjects were positive to anti-HBcAg antibodies. The frequency of asymptomatic carriers of HBsAg went from 4.2% in mexican communities to 17.3% in guatemalan refugee camps, the percentage was higher in households with six or more persons per room (14.0 per 100 individuals). The prevalence of e antigen in subjects positive to HBsAg was higher among guatemalan refugees (35.3%) than among mexicans (7.7%). A refugee camp, Benemerito de las Americas, showed 65.6% positives to anti-HBcAg antibodies and 39.0% asymptomatic HBsAg carriers, 41.7% of these were positive to HBeAg. Antidelta antibodies were present in 50 of 119 subjects positive to HBsAg. The mechanism of transmission was mainly horizontal since most of the infected children in each household corresponded to the oldest offspring. Our data were similar to those observed in the amazonian region of Brazil, Southeast Asia and tropical Africa.